Inovasi Pasta Kulit Pisang dan Microbial Transglutaminase Terhadap pH, Kadar Air, dan Aktivitas Antioksidan Sosis Daging Ayam Petelur Afkir - Nafareza Belvayuna; Juni Sumarmono; Irfan Fadhlurrohman (Jurnal Ilmiah Pangan Halal, 2026)
This study aims to examine the effect of banana peel paste and microbial transglutaminase (MTG) formulations on the pH, moisture content, and antioxidant activity of sausages made from culled laying hens. Meat from culled laying hens has low market value due to its tough texture, thus requiring innovation in its processing. Banana peels were utilized because based on literature they contain protease enzymes that are expected to improve sausage physicochemical quality. The research method used a Completely Randomized Design (CRD) with 4 treatments and 5 replicates: P0 (control), P1 (60% banana peel paste), P2 (1% MTG), and P3 (60% banana peel paste + 1% MTG). The variables observed included pH, moisture content, and antioxidant activity. Data were analyzed using ANOVA and the Honest Significant Differences (HSD) post-hoc test. The results of the statistical analysis showed that the addition of banana peel paste and MTG had no significant effect (p>0.05) on pH (mean 5.92±0.11) and antioxidant activity (mean 55.97±21.13%). However, these treatments had a highly significant effect (p<0.01) on moisture content, with values ranging from 62.92±0.90% to 65.79±1.73%. The formulation of banana peel paste and MTG enzyme effectively increases the moisture content to help improve the physical quality of the sausage without altering the pH value or its antioxidant activity.